A stirring system using suspended magnetically-actuated pillars for controlled cell clustering. Issue 6 (22nd January 2019) - Saberi, Aref; Zhang, Shuaizhong; van den Bersselaar, Carola; Kandail, Harkamaljot; den Toonder, Jaap M. J.; Kurniawan, Nicholas A.
Abstract : We develop a simple, scalable stirring system that can be used for controlled clustering of particles and cells. Abstract : Controlled stirring of a solution is a household task in most laboratories. However, most stirring methods are perturbative or require vessels with predefined shapes and sizes. Here we propose a novel stirring system based on suspended magnetically-actuated pillars (SMAPs), inspired by the ability of biological flagella and cilia to generate flow. We fabricated flexible, millimeter-scale magnetic pillars grafted on transparent polydimethylsiloxane (PDMS) substrates and built a simple actuation setup to control the motion of the pillars remotely. We tested the system with a standard 24-well plate routinely used in most research laboratories and demonstrate that the magnetic actuation results in robust bending of the pillars and large-scale fluid flow in the wells. Quantitative analysis using computational fluid dynamics modeling indicates that the flow profile in the well can be tuned by modulating the applied magnetic field and the geometries of the well and the pillar. Finally, we show that, by employing the stirring system in a standard cell culture plate, we were able to obtain controlled clustering of cells. The SMAP stirring system is therefore a promising cost-effective and scalable stirring approach for various types of studies involving colloids as well as soft and biological materials.